Emerging properties of carbon based 2D material beyond graphene. (10th November 2021) - Jana, Susmita; Bandyopadhyay, Arka; Datta, Sujoy; Bhattacharya, Debaprem; Jana, Debnarayan
Abstract: Graphene turns out to be the pioneering material for setting up boulevard to a new zoo of recently proposed carbon based novel two dimensional (2D) analogues. It is evident that their electronic, optical and other related properties are utterly different from that of graphene because of the distinct intriguing morphology. For instance, the revolutionary emergence of Dirac cones in graphene is particularly hard to find in most of the other 2D materials. As a consequence the crystal symmetries indeed act as a major role for predicting electronic band structure. Since tight binding calculations have become an indispensable tool in electronic band structure calculation, we indicate the implication of such method in graphene's allotropes beyond hexagonal symmetry. It is to be noted that some of these graphene allotropes successfully overcome the inherent drawback of the zero band gap nature of graphene. As a result, these 2D nanomaterials exhibit great potential in a broad spectrum of applications, viz nanoelectronics, nanooptics, gas sensors, gas storages, catalysis, and other specific applications. The miniaturization of high performance graphene allotrope based gas sensors to microscopic or even nanosized range has also been critically discussed. In addition, various optical properties like the dielectric functions, optical conductivity, electron energy loss spectra reveal that these systems can be used in opto-electronic devices. Nonetheless, the honeycomb lattice of graphene is not superconducting. However, it is proposed that the tetragonal form of graphene can be intruded to form new hybrid 2D materials to achieve novel superconducting device at attainable conditions. These dynamic experimental prospects demand further functionalization of these systems to enhance the efficiency and the field of multifunctionality. This topical review aims to highlight the latest advances in carbon based 2D materials beyond graphene from the basic theoretical as well as future application perspectives.